Doppler Effect and It's Cases
Doppler Effect
The apparent change in frequency of sound wave due to the relative motion of source of sound of sound and observer is called Doppler’s effect. For example: You hear the high pitch of the siren of approaching ambulance and you notice dropping of pitch sudenly as ambulance passes you whic is dpppler effect. This phenomenon was first derived by Australian Scientist Doppler. So, it is Doppler’s effect.
Let ‘v’ be the velocity of sound ‘λ’ be the wavelength of sound wave and ‘f’ be the frequency.
$$\text {Then,} \: f = \frac {v}{\lambda } $$
Cases

When source of sound moves towards the Observer in rest
When source of sound moves towards observer in rest, then wavelength of sound decreases. The apparent change in wavelength is given by
\begin{align*} \lambda ‘ &= \frac {v – u_s}{f} \\ \text {If} \: ‘f’' \: \text { be the apparent change in frequency, Then} \\ f’ &= \frac {v}{\lambda ‘} = \frac {v}{(v –v_s)/f} \\ f’ &= \frac {v}{v – u_s} \times f \dots (i) \\ v &= \text {velocity of sound} \\ u_s &= \text {velocity of source} \\ \lambda ‘ &= \text {changed wavelength} \\ f &= \text {frequency of sound wave} \\ \text {Since,} \\ v>v –u_s \: i.e \: f’>f \\ \end{align*}So, frequency increases when source wave is towards the observer in rest. 
When source of sound moves away from the Observer in rest
When source of sound moves away from the observer in rest, the wavelength of sound wave. Therefore, apparent change in wavelength is given by
\begin{align*} \lambda ‘ &= \frac {v +u_s}{f} \\ v &= \text {velocity of sources} \\ u_s &= \text {velocity of sound} \\ \lambda ‘ &= \text {changed wavelength} \\ f &= \text {frequency of sound wave} \\\text {If f’ be the apparent change in frequency.} \\ \text {Then,} \: fi &= \frac {v}{\lambda } = \frac {v}{(v +u_s)/f} \\ f’ &= \frac {v}{v +u_S} \times f \dots (ii) \\ \text {Since,} \\ v<v + u_s \: i.e \: f’<f \\ \end{align*}So, frequency decreases then source moves away from the observer in rest. 
When observer moves towards the source in rest
When observer towards the source in stationary then relative velocity of sound wave to the observer is v +u_{o}.
\begin{align*} f’ &= \frac {\text {relative velocity of sound}}{\text {wavelength}} \\ &= \frac {v + u_0}{v/f} = \left ( \frac {v + u_0}{v} \right ) f \\ \therefore f’ &= \left ( \frac {v + u_0}{v} \right ) f \dots (iii) \\ v +u_0 > v \: i.e \: f’ >f \\ \end{align*} So, frequency increases when observer moves towards the source in rest. 
When observer moves away from the source in rest
When observer moves away from the source in rest then relative velocity of sound wave to the observer is v + u_0.
\begin{align*} f’ &= \frac {\text {relative velocity of sound}}{\text {wavelength}} \\ &= \frac {v  u_0}{v/f} = \left ( \frac {v  u_0}{v} \right ) f \\ \therefore f’ &= \left ( \frac {v u_0}{v} \right ) f \dots (iii) \\ \text {Since, } \\ v u_0 < v \: i.e \: f’ <f \\ \end{align*} So, frequency decreases when observer moves away from the source in rest. 
When source and observer moves towards each other
When the source and observer are approaching towards each other with the velocity u_{s} and u_{o} respectively, then
\begin{align*} \text {velocity of the waves relative to the observer,} v_r = v + u_0, \\ \text {and apparent wavelength,} \lambda ‘ = \frac {v – u_s}{f} \\ \text {Putting these values in equation} \: (v) \: \text {we get} \\ f’ &= \frac {v’}{\lambda ‘} = \frac {v + u_0}{(v – u_s)/f} = \frac {v + u_0}{v –v_s}f \\ \therefore f’ &= \frac {v + u_0}{v –v_s}f \dots (v)\\ \text {Since, } \\ v u_0 < v + u_s \: i.e \: f’ >f \\ \end{align*}So, frequency increases when source and observer towards each other 
When source and observer moves away from each other
When the source and observer moves away from each other with the velocity u_{s} and u_{o} respectively, then
\begin{align*} \text {velocity of the waves relative to the observer,} v_r = v  u_0, \\ \text {and apparent wavelength,} \lambda ‘ = \frac {v + u_s}{f} \\ \text {Putting these values in equation} \: (v) \: \text {we get} \\ f’ &= \frac {v’}{\lambda ‘} = \frac {v  u_0}{(v + u_s)/f} = \frac {v  u_0}{v +v_s}f \\ \therefore f’ &= \frac {v  u_0}{v + v_s}f \dots (vi)\\ \text {Since, } \\ v u_0 < v + u_s \: i.e \: f’ < f \\ \end{align*}So, frequency decreases when source and observer moves away from each other . 
When source leads the observer
When the source and observer moves in same direction and the source is leads the observer, then
\begin{align*} \text {velocity of the waves relative to the observer,} v_r = v + u_0, \\ \text {and apparent wavelength,} \lambda ‘ = \frac {v + u_s}{f} \\ \text {Putting these values in equation} \: (v) \: \text {we get} \\ f’ &= \frac {v’}{\lambda ‘} = \frac {v + u_0}{(v + u_s)/f} = \frac {v + u_0}{v +v_s}f \\ \therefore f’ &= \frac {v + u_0}{v + v_s}f \dots (vii)\\ \text {So, frequency will change depending on}\: u_o \: \text {and} \: u_s. \\ \end{align*}
Manu Kumar Khatry, Manoj Kumar Thapa, Bhesha Raj Adhikari, Arjun Kumar Gautam, Parashu Ram Poudel. Principle of Physics. Kathmandu: Ayam publication PVT LTD, 2010.
S.K. Gautam, J.M. Pradhan. A text Book of Physics. Kathmandu: Surya Publication, 2003.
Things to remember
The apparent change in frequency of sound wave due to the relative motion of source of sound of sound and observer is called Doppler’s effect.
When source of sound moves towards observer in rest, then wavelength of sound decreases. The apparent change in frequency is given by \(f’ = \frac {v}{v – u_s} \times f\).
When source of sound moves away from the observer in rest, the wavelength of sound wave. Therefore, apparent change in frequency is given by \(f’ = \frac {v}{v +u_S} \times f\).
When observer moves towards the source in rest, then apparent change in frequency is given by \( f’ = \left ( \frac {v + u_0}{v} \right ) f\).
When observer moves away from the source in rest then apparent change in frequency is given by \(f’ = \left ( \frac {v u_0}{v} \right ) f\).
When source and observer moves towards each other then apparent change in frequency is given by \(f’ = \frac {v + u_0}{v –v_s}f\).
When source and observer moves away from each other then apparent change in frequency is given by \(f’ = \frac {v  u_0}{v + v_s}f\).
When source leads the observer then apparent change in frequency is given by \(f’ = \frac {v + u_0}{v + v_s}f\).
 It includes every relationship which established among the people.
 There can be more than one community in a society. Community smaller than society.
 It is a network of social relationships which cannot see or touched.
 common interests and common objectives are not necessary for society.
Videos for Doppler Effect and It's Cases
wave and optics acoustic phenomena doppler's effect
wave and optics acoustic phenomena example 2 doppler's effect
wave and optics acoustic phenomena example 3 doppler's effect
wave and optics acoustic phenomena example 4 doppler's effect
wave and optics acoustic phenomena example 5 doppler's effect
wave and optics acoustic phenomena example 8 doppler's effect
wave and optics acoustic phenomena example doppler's effect Part 2